2008
DOI: 10.1099/vir.0.2008/005470-0
|View full text |Cite
|
Sign up to set email alerts
|

CTA1-DD adjuvant promotes strong immunity against human immunodeficiency virus type 1 envelope glycoproteins following mucosal immunization

Abstract: Strategies to induce potent and broad antibody responses against the human immunodeficiency virus type 1 (HIV-1) envelope glycoproteins (Env) at both systemic and mucosal sites represent a central goal for HIV-1 vaccine development. Here, we show that the non-toxic CTA1-DD adjuvant promoted mucosal and systemic humoral and cell-mediated immune responses following intranasal (i.n.) immunizations with trimeric or monomeric forms of HIV-1 Env in mice and in nonhuman primates. Env-specific IgG subclasses in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…In preliminary experiments, we have also found that the adjuvant function of CTA1-DD was independent of TLR signaling, because GC reactions and augmented serum Ab levels were unimpaired in MyD88-and TLR4-deficient mice (J. Mattsson, unpublished observation). These observations confirm previous studies showing that CTA1-DD acted independently of TLR signaling and also had no polyclonal B cell-activating effect in vivo (13,19). In the current study, we consistently failed to demonstrate an effect of CTA1-DD on GC reactions or Ab responses to NP-Ficoll or NP-dextran, responses known to depend on extrafollicular Ab production primarily by B1b cells and possibly MZ B cells (63).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In preliminary experiments, we have also found that the adjuvant function of CTA1-DD was independent of TLR signaling, because GC reactions and augmented serum Ab levels were unimpaired in MyD88-and TLR4-deficient mice (J. Mattsson, unpublished observation). These observations confirm previous studies showing that CTA1-DD acted independently of TLR signaling and also had no polyclonal B cell-activating effect in vivo (13,19). In the current study, we consistently failed to demonstrate an effect of CTA1-DD on GC reactions or Ab responses to NP-Ficoll or NP-dextran, responses known to depend on extrafollicular Ab production primarily by B1b cells and possibly MZ B cells (63).…”
Section: Discussionsupporting
confidence: 77%
“…Although CT and related holotoxins are powerful adjuvants targeted to distinct ganglioside receptors present on all cells of the innate immune system, we do not yet know precisely which cells and how the CTA1-DD adjuvant augments an immune response (15). It improves immune responses to many infectious disease-relevant Ags and by enhancing a wide range of functions from an effective priming of CD8 and CD4 T cells to greatly augmented Ab responses in a TLR-independent manner (13,16). Hence, we have hypothesized that the adjuvant must critically affect key events or processes in the priming of an immune response, possibly through mechanisms that could be different from that of most adjuvants operating via TLR stimulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a unique alternative strategy is the CTA1-DD adjuvant, which hosts the enzymatic activity of the A1 subunit of CT genetically fused to a dimer of the D-fragment of Staphylococcus aureus protein A, CTA1-DD [35]. The CTA1-DD adjuvant targets APCs and has been successfully used in a large number of infectious disease-related immunization protocols in mice and monkeys [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…CTA1-DD has been found to host a broad range of adjuvant functions, greatly augmenting cell-mediated and humoral immune responses to admixed antigen [35]. This effect was TLR/MyD88-independent and comparable in strength to that of CT [36]. However, contrary to CT, CTA1-DD was found to be nontoxic and noninflammatory in mice and monkeys and a promising candidate for use in human vaccines.…”
Section: Mechanisms For Adjuvant Actionsmentioning
confidence: 78%